PERANAN KEMITRAAN GEREJA DENGAN LEMBAGA KRISTEN DALAM MENINGKATKAN PENDAPATAN JEMAAT - Jamsen Ginting; Yanto Paulus Hermanto; Ferry Simanjuntak (Jurnal PKM Setiadharma, 2021)
Poverty in Indonesia is still evident in areas with a large population of Christians. According to the data from the Central Bureau of Statistics in 2020, the provinces of Papua, Maluku and NTT are areas with a high percentage of population poverty rates. Even though in these areas the church has been serving the people for a long time. The existence of the church in the midst of society wherever it is is expected to be able to answer the problem of poverty that plagues church congregants and society in general. Churches that serve in poor community face challenges in playing an active role in increasing congregational income. The limited resources owned by the church and the limited financial support of congregational make the church unable to serve the congregation maximally in terms of supporting the increase in the income of the congregation who are still living in poverty. Unlike the case with churches that have good resources such as human resources and strong financial resources. Realizing the limited resources owned by the church, it is necessary to involve third parties from outside the church and the congregation to equip and provide support to the church in developing the economic potential of the congregation. Keeping Christ-centered Christian values ​​from being degraded, the church builds partnership with institutions that have the same service values ​​as the church and have the same goal of increasing the income of congregation. Cooporation can be carried out through partnerships to achieve common goals to increase income of congregation. Each party has rights and obligations that support each other in the partnership that is built.